Urban-aspects aspects of organization of energy-efficient underground space for protection - Zhidkova, Тetyana; Selikhova, Yana; Kazachenko, Vladislav (Theory and practice of design, 2022)
The war in Ukraine has shown a complete failure to protect civilians. The available bomb shelters are designed to stay for several hours or several days. At the same time, in the cities bordering the aggressor state, bombing and missile strikes hardly stop for weeks and months. People are forced to live in shelters, sleep on the floor in rooms unsuitable for long stays without electricity and water supply, sewerage, heating and internet. This article is aimed at solving urgent, vital problems of protection of the civilian population by creating dual-use premises in the underground space of public buildings. It is proposed to intensify the development of underground spaces, in particular, with the organization of storage facilities for temporary and long-term stay with the use of energy-efficient technologies that will provide people with the necessary resources during the escalation of aggression. To achieve this goal, the following tasks are considered in the course of work: identification of the main ways of development of underground spaces, research of types of organization of storages of different purpose for temporary and long-term stay; disclosure of aspects of energy efficient technologies that will contribute to the energy saving use and provision of resources to residents for a comfortable stay in the underground space. The Department of Urban Construction of the O.M. Beketov National University of Urban Economy in Kharkiv analyzed the underground space of Freedom Square and proposed the organization of a multifunctional shopping and entertainment center connected in the underground passage of subway stations, which will allow access to the complex without access to the ground. On the second floor from the ground should be located dual-use facilities — shopping, entertainment and sports centers, which can very quickly turn into modern bomb shelters.